Pricing the Pharmaceuticals when the Ability to Pay Differs: Taking Vertical Equity Seriously. - Vesa Kanniainen; Juha Laine; Ismo Linnosmaa (Center for Economic Studies and ifo Institute (CESifo), 2019)
A non-trivial fraction of people cannot afford to buy pharmaceutical products at unregulated market prices. Therefore, the paper analyzes the public insurance of the pharmaceutical products in terms of price controls and the socially optimal third-degree price discrimination. It characterizes first the Ramsey pricing rule in the absence of insurance and in the case where the producer price has to cover the R&D sunk cost of the firm. Subsequently, conditions for a welfare increasing departure from Ramsey pricing are stated in terms of price regulation and insurance coverage. The resulting outcome is second best. Unlike the earlier views expressed, increased consumption of pharmaceutical products is shown to be welfare increasing in the second best world. As the optimal means-tested insurance, two alternative criteria for vertical equity are examined in the spirit of the Rawlsian view. In the first scheme, the regulator chooses a higher insurance coverage for individuals with their income below a threshold. In the second scheme, the society imputes a social value to low-income patients in terms of the value-added they produce after the treatment. Under both schemes, the threshold is determined endogenously.
Keywords: L10; L50; 330; pharmaceutical products; price regulation; public health insurance; third-degree price discrimination; equity criterion